Introduction to kinesiology studying physical activity - Brusseau, Timothy A. Jr.; Knudson, Duane V. 1961- (Champaign, IL Human Kinetics, 2022)
"Introduction to Kinesiology: Studying Physical Activity, Sixth Edition, gives students a complete overview of the field of kinesiology and explores the common career paths, questions, and ideas that are part of this discipline. The text stimulates curiosity about the field of kinesiology, gives insight into the subdisciplines of the field, and generates awareness of the current issues that kinesiology professionals seek to understand and solve"--
1. Introduction to kinesiology -- 2. Importance of the physical activity experience -- 3. Philosophy of the physical activity -- 4. History of physical activity -- 5. Sociology of physical activity -- 6. Motor behavior -- 7. Sport and exercise psychology -- 8. Biomechanics of physical activity -- 9. Physiology of physical activity -- 10. Becoming a physical activity professional -- 11. Careers in health and fitness -- 12. Careers in medicine and allied health -- 13. Careers in teaching physical education -- 14. Careers in coaching and sport instruction -- 15. Careers in sport management
Includes bibliographical references and index
Keywords: Kinesiology; Kinesiology -- Study and teaching; Physical education and training